Palliative Care in Advanced Liver Disease: Similar or Different Palliative Care Needs in Patients with a Prospect of Transplantation? Prospective Study from a Portuguese University Hospital and Transplantation Center - da Silva, SNV (2022)
Background and Aims: End-stage liver disease (ESLD) is an important cause of morbidity and mortality, comparable to a large extent to other organ insufficiencies. The need for palliative care (PC) in patients with ESLD is high. In Portugal, in the only identified study, more than 80% of patients hospitalized with ESLD had criteria for PC. No results specified which needs they identified or their transplantation prospect status. Methods: Prospective observational study including 54 ESLD patients who presented to a university hospital and transplantation center, between November 2019 and September 2020. Assessment of their PC needs through the application of NECPAL CCOMS-ICO© and IPOS, considering their transplantation perspective status. Results: Of the 54 patients, 5 (9.3%) were on active waiting list for transplantation and 8 (14.8%) under evaluation. NECPAL CCOMS-ICO© identified 23 patients (n = 42.6%) that would benefit from PC. Assessment of PC needs by clinicians, functional markers and significant comorbidities were the most frequent criteria (47.8%, n = 11). IPOS also revealed a different sort of needs: on average, each patient identified about 9 needs (8.9 ±2.8). Among the symptoms identified, weakness (77.8%), reduced mobility (70.3%), and pain (48.1%) stood out, as well as the psychoemotional symptoms of depression (66.7%) and anxiety (77.8%). There were no significant differences between the subgroups of patients analyzed. Only 4 patients (7.4%) were followed by the PC team. Conclusion: All the ESLD patients included, independently of the group they belonged to, presented with PC needs. No significant differences between the subgroups of patients were identified, confirming that even patients with a transplantation prospect have important needs for PC.